PENGARUH PENDIDIKAN, TEKNOLOGI, DAN INVESTASI ASING LANGSUNG TERHADAP PEREKONOMIAN 5 NEGARA ASEAN - Nawaa, Faizatun; Pudjihardjo, M (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Economic growth is an indicator of a nation's development as indicated by a regular increase in output and is influenced by several factors, including human resources, capital, and technological developments. This study aims to determine the magnitude of the influence of education, technology, and foreign direct investment on the economies of five ASEAN countries from 2005 to 2019. This research is a quantitative study using the panel regression method, with data collection obtained through the World Bank website. The obtained data is then processed and tested through the classical assumption test, which consists of a multicollinearity test, a heteroscedasticity test, and a normality test; and hypothesis testing, which consists of a T-test, F-test, and the coefficient of determination. Tests in the study used the econometric application program, namely Eviews 10. The findings revealed that the education variable, which included government spending on education and enrollment rates in secondary education, internet users, and foreign direct investment inflows, had a positive and significant effect on the economy as measured by GDP. Then government spending on education, enrollment rates in secondary education, internet users, and foreign direct investment inflows simultaneously affect the economy by 96.49%, while the remaining 3.51% is explained by other variables outside the regression equation.